The Symmetric and Asymmetric Effect of Defense Expenditures, Financial Liberalization, Health Expenditures on Sustainable Development - Li Meiling (Frontiers in Environmental Science, 2022)
This study examines the short run, long run, and causal relationships among financial liberalization, healthcare expenditures, and defense expenditures on sustainable development in Pakistan covering the period from 1971 to 2017. The paper also explored the asymmetric relationships among the target variables. To explore these relationships, ARDL and NARDL Models are utilized. Additionally, advanced econometric techniques such as Maki cointegration and quasi-GLS unit root are used to take multiple structural breaks into account. Maki cointegration results show a stable long run relationship between the underlying variables. The findings of ARDL suggest a positive effect of financial liberalization and health expenditures while the negative effect of military expenditures on sustainable development. NARDL estimates suggest strong asymmetry as sustainability responds to positive (negative) shocks in militarization, health expenditures, and financial liberalization differently. The Toda-Yamamoto causality test shows that any policy to target health expenditures and financial liberalization significantly alters sustainable development and vice versa. For robustness checks, FMOLS and alternative proxy of sustainable development are used. The key findings posited the need to shift military expenditures to health expenditures and financial markets to achieve sustainable development goals in Pakistan.